E-Bookstory Media Based on Riri Application on Reading Literacy Skills of Grade III Elementary School Students - Aryani, Kadek Ayu; Antara, Putu Aditya; Trisna, Gusti Ayu Putu Sukma (International Journal of Language and Literature, 2024)
The low reading literacy in elementary schools certainly has an impact on students' academic achievement and intellectual development. Reading literacy. The type of research is a quasi-experimental (Quasi quasi-experimental design) with a pretest-posttest control group design. The population in this study was all Grade III elementary school students using the intact group technique. The number of samples was 61 students, consisting of 24 students in the experimental group and 37 students. The data analysis method used descriptive and inferential statistical analysis. The results showed a t-count value of 2.237, a df 59 significant level of 5%, and a t-table value of 0.023. Based on the calculation achievement, the t-count was greater than the t-table (2.237 more than 0.023) Sig. Value. (2-tailed) less than 0.05 (0.029 less than 0.05). This shows that there is a significant impact between students who learn to use the E-Bookstory media based on the Riri application in grade III elementary school and students who learn reading literacy conventionally in elementary school. This study concludes that the E-Bookstory media based on the Riri application has a significant effect on students' reading literacy. This study implies that the activities The purpose of this study is to analyze the use of E-Bookstory learning media in developing learning must be able to condition students to be more active in reading.